Open Educational Resources: Challenges and Opportunities in Indian Primary Education - Ganapathi, Janani (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
Education is a fundamental human right, yet one fifth of the world’s population lives with poor literacy. India is home to the largest number of illiterate people, with infrastructural, cultural, and socio-economic factors hindering equitable access to quality education. Due to the rapidly growing technology and Internet usage in the country, open educational resources (OER) are increasingly being used as a vital tool to help transcend barriers to child literacy, also aiding in educational attainment. While an array of scholarly works provides evidence of the potential in OER to influence higher education outcomes in developing nations, academic analysis of their impact on primary level education attainment has been minimal. This paper retrieve lessons from three children’s content providing organizations to understand the opportunities and challenges of OER in primary-level education in developing nations with similar cultural, infrastructural, and socio-economic issues. While the findings of this study suggest that the use of OER allows for greater distribution and scale across different cultural and linguistic settings, particularly in rural and remote regions, they also warn against the adaptation and pedagogical barriers of OER into societies where traditional modes of education are established and trusted.